GOOD UNIVERSITY GOVERNANCE UNTUK MENINGKATKAN EXCELLENT SERVICE DAN KEPERCAYAAN MAHASISWA AKUNTANSI (Studi Kasus Mahasiswa Program Studi Akuntansi UISU dan UMN) - Zenni Riana; Ulva Ayuningtias Tarigan (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2019)
This research was conducted at Accounting Students at the Islamic University of North Sumatra and Accounting Students at the Muslim University of Nusantara Al-Washliyah. The purpose of this study was to analyze the effect of Good University Governance to Improve the Excellent Service and Trust of Accounting Students (Case Study of Accounting Study Students at UISU and UMN). Research data obtained from questionnaires containing independent variables and dependent variables that have been distributed to stambuk 2016 accounting students as respondents in this study.The population in this study were stambuk 2016 Accounting Students, amounting to 266 respondents consisting of Accounting Students from the Islamic University of North Sumatra Meda and Muslim University Nusantara Al-Washliyah Medan. The sample collection technique uses a method using Slovin Technique. Data collection techniques use Library Research and Field Research. The data analysis technique used is Descriptive Statistics Analysis, Data Trends, Validity Test, Reliability Test, Normality Test, Linearity Test, Heteroscedasticity Test, Simple Linear Regression Test, and t Test.The type of research used is Descriptive Analysis Technique using software or application spss version 20. The results of the study are: 1) Good university governance has a positive and significant effect on excellent service. 2) Good university governance has a positive and significant effect on trust.